Navigating Local Wisdom and National Language Policy: A Case Study of Classroom Interaction Dynamics - Waluyo, Bagus (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
The Indonesian education system demands the use of the national language in formal situations, posing a dilemma in Blitar schools where teachers and students typically utilize Blitar Javanese alongside Indonesian. This study analyzes the reasons underlying this linguistic choice in classroom interactions using a qualitative single-case study design. Twelve self-selected instructors participated in two weeks of online interviews during COVID-19 to gather data. The results highlight the importance of Blitar Javanese in conserving local knowledge and show that it promotes comfortable and active communication in classroom environments. This study emphasizes methods for preserving regional linguistic history in educational settings while utilizing language effectively